Kebiasaan Membaca Siswa Sekolah Dasar (Survei Aspek Kebiasan Membaca Siswa SD Negeri 2 Pinggirsari di Desa Pinggirsari Kecamatan Arjasari Kabupaten Bandung) - Windi Rahayu; Yunus Winoto; Asep Saeful Rahman (Program Studi Ilmu Perpustakaan UIN Alauddin, 2016)
The study is aimed to know students reading habits in the government primary school 2 Pinggirsari located in Pinggirsari village, District of Bandung. It is a descriptive survey research. The population of the study were students who now in 3rd-6th grades. Sampling was used by using census method. The questionaires, interview, observation, and library research were used to gather data. Based on the research findings, it is found that the students were happy once they found books in the library school; the students usually read book three times a week and spent more than 15 minutes to read; in a week, they read three books and magazines 1-5 titles; most of the collections were found from their school library; frequently, they visit library/reading area in around two times a week.